Regulating the old game of smuggling? Coltan mining, trade and reforms in the Democratic Republic of the Congo. Issue 3 (6th August 2018) - Wakenge, Claude Iguma; Dijkzeul, Dennis; Vlassenroot, Koen
Abstract: This article examines the smuggling of coltan into and out of artisanal mining areas in northern Katanga where the ITRI Tin Supply Chain Initiative (iTSCi), a policy on conflict minerals, tries to improve transparency in trading tin, tantalum (coltan) and tungsten. The article approaches smuggling from a sociology of economic life perspective, closely examining how and why artisanal miners and mine-based middlemen ( négociants ) helped smugglers ( hiboux ) in the trafficking of coltan. The findings indicate that the social networks in which miners and mine-based négociants are embedded allow the miners, négociants and smugglers to maintain close relationships and to breach official regulations, but miners and mine-based négociants also rely on the same networks to cheat in their dealings with the smugglers. This article concludes that, rather than considering coltan mining areas to be 'enclaves of regulations', understanding and addressing smuggling at both local and broader contexts call for a comprehensive, more contextualised approach.